The Effect of Perceived Effort on Reward Valuation: Taking the Reward Positivity (RewP) to Dissonance Theory - Harmon-Jones, Eddie; Clarke, Daniel; Paul, Katharina; Harmon-Jones, Cindy (Frontiers in Human Neuroscience, 2020)
The present research was designed to test whether the subjective experience of more effort related to more reward valuation as measured by a neural response. This prediction was derived from the theory of cognitive dissonance and its effort justification paradigm. Young adult participants (n = 82) engaged in multiple trails of a low or high effort task that resulted in a loss or reward on each trial. Neural responses to the reward (loss) cue were measured using EEG, so that the event-related potential known as the Reward Positivity (RewP) could be assessed. Results revealed no significant differences between low and high effort conditions on the RewP. However, within the high effort condition, a more subjective experience of effort was associated with a larger RewP. This research extends past research on the effort justification paradigm of cognitive dissonance theory by suggesting that effort justification is associated with an implicit measure of reward valuation. It therefore challenges recent perspectives on dissonance processes that posit that these evaluative changes should only occur on explicit but not implicit measures.